Law and the Christian tradition in modern Russia
1 online resource (xiv, 339 pages).
Keywords: "This book focuses on a vibrant central current within the history of Russian legal thought: how Christianity, and theistic belief generally, has inspired the aspiration to the rule of law in Russia, informed Russian philosophies of law, and shaped legal practices. In this volume, a team of Western and Russian scholars presents fourteen concise, non-technical portraits of modern Russian jurists and philosophers of law whose thought was shaped significantly by Orthodox Christian faith or theistic belief. Each portrait provides essential biographical information, a description of the jurist's religious views, and a substantive account of the subject's jurisprudential ideas. Each chapter ends with a word about the jurist's legacy in Russia today. The collection embraces the most creative period of Russian legal thought, the century and a half from the later Enlightenment to the Russian emigration following the Bolshevik Revolution and Civil War of 1917-1921. While many of the figures represented in this gallery were liberals, in various sense of the term, the volume reaches across the ideological spectrum. Contributors to the volume include respected senior authorities together with younger scholars of exceptional promise. This book will merit the attention of anyone interested in exploring the connections between law and religion in modern times"--